(untitled) (Research, Society and Development, 2022)
The purpose of this work was to characterize, through analytical methods, the physicochemical and toxicological properties between commercial polystyrene and recycled polystyrene. The characterization of the respective products was started with X-Ray Fluorescence (FRX), Thermogravimetric Analysis (TGA) and Differential Scanning Calorimetry (DSC). The in vitro analysis of toxicity in microcrustacean Artemia salina was carried out. The FRX analyzes indicated the presence of chlorine and bromine in the commercial PS. It was observed that recycled PS presents greater thermal stability when compared to commercial PS. No toxicity results were observed for the two types of samples cited in this research.